2015
DOI: 10.1021/acsami.5b08399
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Analysis of Gas Generation in Lithium-Ion Batteries with Different Carbonate-Based Electrolytes

Abstract: Gas generation in lithium-ion batteries is one of the critical issues limiting their safety performance and lifetime. In this work, a set of 900 mAh pouch cells were applied to systematically compare the composition of gases generated from a serial of carbonate-based composite electrolytes, using a self-designed gas analyzing system. Among electrolytes used in this work, the composite γ-butyrolactone/ethyl methyl carbonate (GBL/EMC) exhibited remarkably less gassing because of the electrochemical stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 22 publications
(39 reference statements)
2
55
0
Order By: Relevance
“…4 shows the gas production of the cells after 50th and 200th cycles under different charging rates. Gas generation during cell aging is mainly from the decomposition of the electrolyte at the electrode/electrolyte interfaces [36][37][38]. A general trend in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…4 shows the gas production of the cells after 50th and 200th cycles under different charging rates. Gas generation during cell aging is mainly from the decomposition of the electrolyte at the electrode/electrolyte interfaces [36][37][38]. A general trend in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The gas generation was considered as a detrimental phenomenon because of the caused elevated pressure and tempera- [181]. The result of gas analysis system shown that the composite GBL/EMC displayed a distinctly reduced gas liberation in comparison with other solvents.…”
Section: Probing Gas Reactions During Battery Operationmentioning
confidence: 99%
“…Serious electrolyte decomposition will occur when the layered ternary oxide cathode materials are charged to a higher voltage due to the narrow voltage windows of commercialized electrolyte and chemical oxidation of electrolyte solvents caused by active oxygen, [ 80‐81 ] which will not only consume available Li ions from the electrolyte and cathodes and form high impedance surface layer under high‐voltage operating conditions, [ 82‐84 ] but also result in electrolyte depletion and gas generation. [ 85‐86 ] For example, by the decomposition process, LiPF 6 will be resolved into LiF and PF 5 , as indicated in equation (1). [ 87 ] LiF will increase the cathode impedance and the PF 5 will tend to react with the H 2 O to generate HF as indicated in equation (2).…”
Section: Failure Mechanismsmentioning
confidence: 99%